2015
DOI: 10.1111/cen.12946
|View full text |Cite
|
Sign up to set email alerts
|

Association of low baseline free thyroxin levels with progression of coronary artery calcification over 4 years in euthyroid subjects: the Kangbuk Samsung Health Study

Abstract: In this cohort of euthyroid men and women, a low baseline FT4 level was associated with a high risk of CACS progression over 4 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…This study showed that, although their thyroid function was within the normal range, the non-obese AIT patients had relatively lower FT3 and FT4 levels, and higher TSH than the controls. A recent cohort study from the euthyroid population showed that a low baseline FT4 level was associated with a high risk of the progression of coronary artery calcification over 4 years ( 18 ). An in vitro study also found that T3 inhibits the calcification and phenotype transformation of vascular smooth muscle cells ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that, although their thyroid function was within the normal range, the non-obese AIT patients had relatively lower FT3 and FT4 levels, and higher TSH than the controls. A recent cohort study from the euthyroid population showed that a low baseline FT4 level was associated with a high risk of the progression of coronary artery calcification over 4 years ( 18 ). An in vitro study also found that T3 inhibits the calcification and phenotype transformation of vascular smooth muscle cells ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this concept, low-normal thyroid function is associated with a greater increased intima media thickness (cIMT), an established biomarker of subclinical atherosclerosis [3, 4]. Furthermore, low-normal thyroid function is associated with increased coronary artery calcification [5] and progression thereof [6], although an association of a high-normal TSH level with increased coronary heart disease risk has been variably reported [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this concept, low-normal thyroid function associates with increased intima media thickness (cIMT), an established marker of subclinical atherosclerosis [4,5]. Moreover, it was documented recently that low-normal thyroid function is associated with progression of coronary artery calcification [6,7], although a high-normal TSH level is unlikely to predict new onset clinically manifest coronary heart disease [8].…”
Section: Introductionmentioning
confidence: 94%